Identification of Critical Genes and Proteins for Stent Restenosis Induced by Esophageal Benign Hyperplasia in Esophageal Cancer - Weng, Li; Shen, Shanshan; Wu, Shaoqiu; Yin, Xiang; Liu, Bingyan; Shang, Mingyi; Zou, Xiaoping; Mao, Aiwu (Frontiers in Genetics, 2020)
This study was conducted to explore the potential genes and proteins associated with esophagus benign hyperplasia induced by esophageal stents. Five patients with esophageal cancer subjected to esophageal stent placement were enrolled in this study. Long non-coding RNA (lncRNA) sequencing and tandem mass tag quantitative proteomics analysis were performed by using the collected hyperplastic samples and adjacent non-hyperplastic tissues. Differentially expressed (DE) RNAs and proteins were analyzed, followed by functional enrichment analysis, protein-protein interaction (PPI) network analysis, and competitive endogenous RNA (ceRNA) network construction. Venn analysis was performed to extract the overlaps between DE mRNAs and DE proteins and the expression correlations between DE mRNA and proteins were analyzed. Results showed that total 642 DE RNAs (457 mRNA and 185 lncRNAs) and 256 DE proteins were detected. DE mRNAs (such as MAOB, SDR16C5, and FOSL1) were enriched in oxidation-reduction process-associated functions. PPI network was comprised of 175 nodes and 425 edges. VEGFA was a significant node with the highest degree. LncRNA-mRNA network with three subnetworks (C1, C2, C3) was constructed for lncRNAs with more than 15 gene targets. RP11-58O9.2 was a significant lncRNA with the most target genes and RP11-667F14.1 regulated more than 20 targets. FOSL1 was a common target of the two lncRNAs. Function analysis showed that DE lncRNAs were involved in the HTLV-I infection (RP11-58O9.2 and RP11-667F14.1) and IL-17 signaling pathways (RP11-5O24.1 and RP11-58O9.2). Total 11 DE mRNAs were overlapped with DE proteins, among which MAOB and SDR16C5 showed positive correlations between mRNA and protein expression. Function analysis showed that MAOB was enriched in oxidation-reduction process and its protein was closely related with response to lipopolysaccharide. VEGFA, FOSL1, MAOB, SDR16C5, RP11-58O9.2, RP11-667F14.1, and RP11-288A5.2 may be served as genetic targets for preventing stent restenosis in esophageal cancer.